STRATEGI PENGELOLAAN PENDIDIKAN ANAK USIA DINI DI RA NURUL ULUM GADUNGAN KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Anjani Hikmatul Maula; Muhammad Hanif; Yorita Febry Lismanda (UNISMA, 2020)
Early childhood education institution is an institution that is responsible for guiding the growth and development of children from birth until the age of six years. Lately, the growth and development of early childhood education institution has increased rapidly. However, the growth and development of early childhood education institution is still not balanced with optimal management of education. To overcome this problem, researchers conducted research on RA Nurul Ulum education institutions in the village of Gadungan-Poncokusumo Malang. This research uses descriptive qualitative research. After conducting further research, the Management of Early Childhood Education at RA Nurul Ulum is carried out professionally, innovatively, and in accordance with the characteristics and aspects of child development.